Aquaporin-7 Deficiency Attenuates Liver Fibrosis by Inhibiting the Activation and Proliferation of Hepatic Stellate CellsSummary - Junqi Zhang; Yijun Ma; Yu Wang; Chi Zhang; Peng Chen; Qing Ye; Yueyue Lei; Yanghao Li; Bo Zhang; Tonghui Ma (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Aquaporin-7 (Aqp7) is an aquaglyceroporin that provides transmembrane gateway of water, glycerol, and hydrogen peroxide (H2O2). Analysis of the Gene Expression Omnibus (GEO) database revealed upregulation of hepatic AQP7 expression in liver fibrosis patients. This study aimed to elucidate the role of Aqp7 in the pathogenesis of liver fibrosis. Methods: The GEO database analysis and TGFβ -induced human hepatic stellate cell (HSC) line LX-2 cells were used to study the relevance of AQP7 to human liver fibrosis. Bile duct ligation-induced and carbon tetrachloride-induced liver fibrosis models were employed to investigate the role of Aqp7 in liver fibrosis formation in conventional and HSC-specific Aqp7 knockout mice. Primary mouse HSCs were isolated to explore the role of Aqp7-mediated glycerol and H2O2 transport in HSC activation and proliferation. Results: AQP7 mRNA and protein levels are remarkably upregulated in TGFβ-induced LX-2, as well as in primary mouse HSCs isolated from liver fibrosis models induced by bile duct ligation and peritoneal injection of carbon tetrachloride. Liver fibrosis formation was significantly alleviated in both conventional and HSC-specific Aqp7 knockout mice compared with their respective wild-type littermates, as evidenced by significantly decreased deposition of fibrous extracellular matrix. Aqp7 deletion resulted in the accumulation of intracellular glycerol, an increase in triglyceride content, the retention of intracellular lipid droplets, and dilatory activation of HSCs. Moreover, Aqp7 deficiency led to elevated intracellular H2O2 levels during activation, which impaired autophagy, proliferation, and survival of HSCs by disrupting relevant cell signaling pathways. Virus-mediated replacement with glycerol- or H2O2-transporting aquaporins Aqp3 or Aqp8, but not the strictly water-selective channel Aqp4, effectively rescued the impaired activation and proliferation in primary cultured Aqp7-/- HSCs. Conclusions: Our findings suggest that Aqp7 plays a crucial role in the activation of HSCs and the formation of liver fibrosis by regulating triglyceride catabolism and maintaining reactive oxygen species homeostasis in HSCs.